Results-Based Management As A Model for Madrasah Education Management - Aslamiyah, Nurul; Patimah, Siti; Murtafiah, Nurul Hidayati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study aims to: (1) analyze the planning and implementation of RBM in the management of madrasah education, (2) examine the mechanism for evaluating and measuring the achievement of results, and (3) identify the supporting and inhibiting factors for the implementation of RBM and its implications for the formulation of madrasah education management models. This study uses a qualitative method with a multisite approach. The research locations include three private aliyah madrassas in South Lampung Regency, namely MAS Al Fatah Natar, MAS Hidayatul Mubtadiin Jati Agung, and MAS Islamiyah Cintamulya. Data was obtained through in-depth interviews, observations, and documentation studies of madrasah heads, deputy madrasah heads, and teachers. Data analysis was conducted using an interactive model, involving data reduction, presentation, and drawing conclusions, which were validated through the triangulation of sources and techniques. The study's results reveal variations in the level of maturity of RBM implementation among madrasas. MAS Al Fatah Natar implements RBM relatively more systematically, utilizing academic outcome indicators and data-based follow-up. In contrast, MAS Hidayatul Mubtadiin Jati Anonacademicout achieves nonacademic outcomes through the program. At the same time, Tion, while MAS Islamiyah Cintamulya is still situational and has not been institutionalized. The conclusion of the study emphasizes that the clarity of outcome indicators, consistency of data-based evaluation, and follow-up documentation are the keys to the success of RBM in madrasas.